Patient, surgical and clinical factors associated with longer stay in the Post Anaesthesia Care Unit - Briggs, Karen; Botti, Marri; Phillips, Nicole; Bowe, Steven; Street, Maryann (Operating Room Nurses Association of Canada Journal, 2024)
Aim: To explore patient, surgical and clinical factors associated with readiness- for-discharge and total length of stay in the Post Anaesthesia Care Unit (PACU). Background: Longer stay in the PACU decreases the flow of patients and is associated with increased risk of adverse events. The time to readiness-for- discharge reflects clinical parameters associated with patient flow in the PACU independent of system delays. Methods: This retrospective cohort study included a randomly selected sample of 244 post-surgical patients admitted to a large private, Australian health service. Results: The median and average times to readiness-for-discharge were 48 minutes and 56 minutes respectively with a range from 9 to 175 minutes. The total length of stay in the PACU had median and average times of 66 minutes and 73 minutes respectively. Five independent factors associated with longer time to readiness-for-discharge identified in multivariable modelling were: age, surgery duration, post-operative nausea and vomiting, administration of opioids and medical consultation. Additional factors that were determined from univariate analyses to be associated with longer time to readiness-for-discharge from the PACU were hypothermia, moderate or severe pain, major surgery and neurological surgery. Conclusion: This study found that modifiable and non-modifiable factors are associated with time to readiness-for-discharge. The findings provide a focus for the clinical care of patients in the PACU to optimise the time to readiness- for-discharge and increase patient flow. Understanding factors associated with longer stay helps efficient management of staffing levels and patient flow within the PACU, to improve the quality of care provided.